2016
DOI: 10.1007/s12663-016-0959-6
|View full text |Cite
|
Sign up to set email alerts
|

Trigemino-Cardiac Reflex: A Phenomenon Neglected in Maxillofacial Surgery?

Abstract: Background Trigemino-cardiac reflex is a physiologic response of the body to pressure effects in the region of distribution of the trigeminal nerve. Oral and maxillofacial surgical procedures can induce the development of this reflex, which leads to significant changes in the heart rate and sinus rhythms. This study intends to evaluate the effects of this reflex in patients with facial fractures and its subsequent management. Patients and Methods A total of thirty-seven patients with facial fractures who repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
(12 reference statements)
2
18
0
Order By: Relevance
“…While TCR is generally expressed as bradycardia,6 this case is notable in that prominent supraventricular arrhythmia first appeared and led to bradycardia; accordingly, intravenous lidocaine and an anticholinergic agent were administered simultaneously, instead of anticholinergic agents alone, and were protective. Although TCR rarely occurs in orthognathic surgery, with a reported incidence of 1%–2%,7 clinicians should be aware of the possibility of TCR and able to judge and manage it promptly.…”
Section: Discussionmentioning
confidence: 90%
“…While TCR is generally expressed as bradycardia,6 this case is notable in that prominent supraventricular arrhythmia first appeared and led to bradycardia; accordingly, intravenous lidocaine and an anticholinergic agent were administered simultaneously, instead of anticholinergic agents alone, and were protective. Although TCR rarely occurs in orthognathic surgery, with a reported incidence of 1%–2%,7 clinicians should be aware of the possibility of TCR and able to judge and manage it promptly.…”
Section: Discussionmentioning
confidence: 90%
“…TCR, a sudden decrease in pulse rate i.e., bradycardia and mean arterial blood pressure (MABP) but also apnoea and gastric hypermotility during stimulation of any branches of the trigeminal nerve. The pressure induced by the neural reflexes on the trigeminal nerve causes vagal stimulation leading to bradycardia [ 1 , 2 ]. In 1987, Bainton and Lizi [ 3 ], and Loewinger et al [ 4 ], suggested that TCR can be elicited by stimulating afferent paths other than the ciliary nerves (branches of the ophthalmic division of the trigeminal nerve) which are classically associated with the oculocardiac reflex .…”
Section: Discussionmentioning
confidence: 99%
“…Trigeminocardiac reflex (TCR) which was traditionally known as the oculocardiac reflex is a rare physiologic phenomenon that can be seen during a surgical procedure in the maxillofacial region. TCR was first observed by Kratschmer in 1870 [ 1 ]. Later, in 1908 a peripheral variant of TCR was observed by Aschner and Dagini and hence was then popularly known as Aschner-Dagini Reflex.…”
Section: Introductionmentioning
confidence: 99%
“…TCR most commonly occurs in maxillofacial surgery and direct traction stimulation of the trigeminal nerve branches during neurosurgery. TCR has been reported occasionally in skull base surgery and maxillofacial surgery [ 5 , 6 ]. It commonly happens in endoscopic sinus surgery with nasal packing or transsphenoidal approach for resection of pituitary adenomas [ 7 ].…”
Section: Discussionmentioning
confidence: 99%